Efficient computation of functional brain networks: towards real-time functional connectivity - García-Prieto, Juan; Bajo, Ricardo; Pereda, Ernesto (Frontiers in Neuroinformatics, 2017)
Functional Connectivity has been demonstrated to be a key tool for unravelling how the brain balances functional segregation and integration properties while processing information. This work presents a set of open-source tools that significantly increase computational efficiency of some well-known connectivity indices and Graph-Theory measures. PLV, PLI, ImC and wPLI as Phase Synchronization measures, Mutual Information as an information theory based measure and Generalized Synchronization indices are computed much more efficiently than prior open-source available implementations. Furthermore, network theory related measures like Strength, Shortest Path Length, Clustering Coefficient and Betweenness Centrality are also implemented showing computational times up to thousands of times faster than most well-known implementations. Altogether, this work significantly expands what can be computed in feasible times, even enabling whole-head real-time network analysis of brain function.